Work stress among expatriate managers in Malaysia's government-linked companies - Jedin, Mohd. Haniff (2013)
Due to the rapid increase in demand for skillful and experienced managers, many multinationals including Malaysian conglomerate companies under the umbrella of Khazanah Nasional Berhad which also known as the government-linked companies (GLCs) had employed expatriates in their workplaces especially in IT, engineering and elite positions such as management directors that really focus on restructuring and developing healthy business growths.In fact, their expertise and experience had improved many GLCs performance.However, many of them are exposed to work stress that could jeopardise the performance of the Malaysian GLCs.Thus, this study aims to explore such phenomenon related to work stress at workplace.Workload, role conflict and interpersonal relationship are among the factors that influence the work stress at workplace. Expatriates who are attached with Malaysia's government-linked companies such as UEM Group, Silterra, Telekom Malaysia, Tenaga Nasional Berhad, ASTRO, ClMB Group and Celcom Axiata were used as the main database in this study. A total of 90 useable qestionnaires were received.Result shows that workload and interpersonal relationships were significant but on the other hand role conflict was not a significant factor to influence work stress among the expatriates who are attached with Malaysian GLCs.